The influence of price on seaweed farming growth: A case of East coast region of Zanzibar. - Seif, Riziki S. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of of Degree Master's of Business Administration in Corporate Management ((MBA-CM) of Mzumbe University